Chrząszcze wodne (Coleoptera: Hydradephaga, Hydrophiloidea, Hydraenidae, Dryopoidea) Puszczy Knyszyńskiej - Czesław Greń; Krzysztof Lubecki; Krzysztof Sućko (Zenodo, 2022)
Water Beetles (Coleoptera: Hydradephaga, Hydrophiloidea, Hydraenidae, Dryopoidea) of the Knyszyn Primeval Forest, NE Poland. Compared to other forest complexes in the Podlasie region (NE Poland), the water beetle fauna of the Knyszyn Primeval Forest (KPF) is very poorly known. The authors’ fieldwork in the KPF in 2020-2021 yielded a total of 3 212 water beetles from 128 species, 116 of these being first records for the KPF. The addition of the 9 species already reported in the literature from this area but not caught during the present fieldwork gives a total of 137 water beetle species from 11 families for the KPF. This number makes up 37.5% of the total number of species from these families known to occur in Poland. The relatively good state of preservation of the Knyszyn Forest, the high degree of afforestation, the existence of specific micro-environments and the significant percentage of peatlands all mean that rare and interesting species of beetles can be expected there. Of particular note are the boreal/taiga species Agabus striolatus (Gyllenhal, 1808), Hydroporus brevis F. Sahlberg, 1834 and Ilybius wasastjernae (CR Sahlberg, 1824). The following seven species found in the Knyszyn Forest are on the national Red List (Pawłowski et al. 2002): Hydroporus brevis (threat category VU), Hydroporus elongatulus (VU), Ilybius wasastjernae (VU), Hydroporus morio (EN), Agabus striolatus (NT), Hydrophilus piceus (NT) and Cercyon tristis (LC). These and other interesting species are discussed in the Discussion and Conclusions. The data acquired during this study confirm the high natural value of the KnyszyN Forest as a refuge of rare, stenotopic species of water beetles.